'Chancing on a spectacle:' co‐occurring animal migrations and interspecific interactions. Issue 11 (31st March 2020) - Cohen, Emily B.; Satterfield, Dara A.
Abstract : Migrations of diverse wildlife species often converge in space and time, with their journeys shaped by similar forces (i.e. geographic barriers and seasonal resources and conditions); we term this 'co‐migration'. Recent studies have illuminated multi‐speciesmigrations by land and sea including the simultaneous movements of numerous insects, birds, bats and of fish invertebrates marine predators. Beyond their significance as natural wonders, species with overlapping migrations may interact ecologically, with potential effects on population and community dynamics. Direct and indirect ecological interactions (including predation and competition) between migrant species remain poorly understood, in part because migration is the least‐studied phase of animals' annual cycles. To address this gap, we conducted a literature review to examine whether animal migration studies incorporate multiple species and to what extent they investigate interspecific interactions between co‐migrants. Following a key word search, we read all migration research papers in 23 relevant peer‐reviewed journals during 2008–2017. Thirty percent of animal migration papers reported two or more species with coinciding migrations, suggesting that co‐migrations are common, although few studies investigated or discussed these mixed‐species migrations further. Synthesizing these, we present examples and describe five types of ecological interactions between migrating species, including predator–prey, host–parasite and commensal relationships. Considering migratory animals as interacting with migrant communities will enhance understanding of the drivers of migration and could improve predictions about wildlife responses to global change. Further research focused on multi‐species migrations could also inform conservation efforts for migratory animal populations, many of which are declining or shifting, with unexplored consequences for other co‐migratory species.